SS Cygni Revisited - R. C. Smith; J. Echevarrıa; J. V. Hernandez; P. Szkody (Acta Polytechnica CTU Proceedings)
New spectroscopic and photometric observations of SS Cygni, the brightest dwarf nova system, have been obtained, with the aim of mapping starspots on the surface of the secondary star. Four nights of echelle spectroscopy in quiescence have been obtained using the 2.2-m telescope at San Pedro Martir (Mexico) in August 2012 and another two nights at the 3.5-m telescope at Apache Point Observatory, USA, in September 2012, but these data are still being reduced. Simultaneous CCD photometry was also obtained at the two sites, and the Mexican photometry was extended into the subsequent long outburst. This presentation reveals some interesting photometric behaviour in that outburst, but further data will be necessary before the nature of the behaviour can be determined.